PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS KEARIFAN LOKAL KOTA PALEMBANG PADA MATERI KEKAYAAN BUDAYA DI SD NEGERI 6 PALEMBANG - iraoctaagustiani; Hermansyah; Mega Prasrihamni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research and development aims to produce interactive learning media based on local wisdom of Palembang city on cultural wealth material that is valid, practical, and effective for fourth grade students at SD Negeri 6 Palembang. The methodology used in this study is the type of Research and Development (RnD) research, using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The population in this study were all fourth grade students of SD Negeri 6 Palembang. The sample in this study was 25 students of class IV.B. Data collection techniques used were observation, interviews, tests, questionnaires, and documentation. This study produced interactive multimedia learning media based on the local wisdom of Palembang city. Data analysis techniques were carried out by analyzing validity, practicality and effectiveness. Based on the results of the study, data analysis can be proven through the results of the validity assessment on the media validation aspect which obtained a percentage of 93.7%, on the material validation aspect obtained a percentage of 93.7%, and on the language validation aspect obtained a percentage of 94%, with the category